Circular RNA CHST15 Sponges miR-155-5p and miR-194-5p to Promote the Immune Escape of Lung Cancer Cells Mediated by PD-L1 - Yang, Jianru; Jia, Yang; Wang, Bing; Yang, Shengrong; Du, Kun; Luo, Yujie; Li, Yunhe; Zhu, Bing (Frontiers in oncology, 2021)
The effects of up-regulated CircCHST15 on lung cancer remained unclear. In this study, the role of CircCHST15 in lung cancer was investigated. Dual-luciferase reporter verified the bioinformatics prediction that CircCHST15 targeted miR-155-5p and miR-194-5p. The correlation between CircCHST15 and PD-L1 was analyzed by Pearson analysis. CCK-8 and colony formation was performed to determine the viability and proliferation of lung cancer cells. After the lung cancer (subcutaneous-xenotransplant) model was established in mice, the T cell subtype and related cytokines in mouse tumor tissues were detected by flow cytometry and ELISA. Moreover, the expressions of CircCHST15, miR-155-5p, miR-194-5p, immune-related, and proliferation-related factors of the lung cancer cells or mice tumor tissues were detected by immunohistochemistry, RT-qPCR, or Western blot. CircCHST15 and PD-L1 were high-expressed in lung cancer, and the two was positively correlated. CircCHST15 targeted miR-155-5p and miR-194-5p, the later further targeted PD-L1. Lung cancer cell viability and proliferation were increased by miR-155-5p and inhibited by miR-194-5p. CircCHST15 located in the cytoplasm promoted tumor growth, down-regulated the expressions of miR-155-5p and miR-194-5p, and up-regulated the expressions of PD-L1, Ki-67, PCNA, CCL17, CCL22, IFN-γ, TNF-β, and IL-10. Also, CircCHST15 decreased the CD8 cells in mouse blood and tumor, but increased the Tregs in mouse tumor. PD-L1 inhibitor showed an opposite effect to CircCHST15 on mouse tumors. CircCHST15 sponged miR-155-5p and miR-194-5p to promote the PD-L1-mediated immune escape of lung cancer cells.